Ẩn danh

P = \(\left(\dfrac{x-2}{x+2\sqrt{x}}+\dfrac{1}{\sqrt{x}+2}\right).\dfrac{\sqrt{x}+1}{\sqrt{x}-1}\) với x > 0, x ≠ 1

Chứng minh P = \(\dfrac{\sqrt{x}+1}{\sqrt{x}}\)

\(P=\left(\dfrac{x-2}{x+2\sqrt{x}}+\dfrac{1}{\sqrt{x}+2}\right)\cdot\dfrac{\sqrt{x}+1}{\sqrt{x}-1}\)

\(=\left(\dfrac{x-2}{\sqrt{x}\left(\sqrt{x}+2\right)}+\dfrac{1}{\sqrt{x}+2}\right)\cdot\dfrac{\sqrt{x}+1}{\sqrt{x}-1}\)

\(=\dfrac{x-2+\sqrt{x}}{\sqrt{x}\left(\sqrt{x}+2\right)}\cdot\dfrac{\sqrt{x}+1}{\sqrt{x}-1}\)

\(=\dfrac{\left(\sqrt{x}+2\right)\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)\cdot\sqrt{x}}=\dfrac{\sqrt{x}+1}{\sqrt{x}}\)

Bình luận (0)

Các câu hỏi tương tự
Nguyễn Thị Thu Phương
Xem chi tiết
minh ngọc
Xem chi tiết
Ngọc Vũ
Xem chi tiết
....
Xem chi tiết
Yết Thiên
Xem chi tiết
Nhân Nguyễn
Xem chi tiết
Nguyễn Thị Thu Phương
Xem chi tiết
manh
Xem chi tiết
Hoàng Tiến Long
Xem chi tiết
2012 SANG
Xem chi tiết